Pacific currents : the responses of U.S. allies and security partners in East Asia to China's rise - Medeiros, Evan S.; Crane, Keith; Heginbotham, Eric; Levin, Norman D.; Lowell, Julia, 1961-; Rabasa, Angel; Sŏng, So-mi (Rand Corporation monograph series., 2008)
China's economic, military, and diplomatic power has been on the rise, and many worry that it is nudging aside U.S. influence in the Asia-Pacific region. To explore this issue, the authors examined six specific U.S. allies and partners--Australia, Japan, the Philippines, Singapore, South Korea, and Thailand. From extensive in-country interviews, trade and poll data, etc., they examined the responses in each nation to China's rise and assessed the implications for U.S. regional security interests. The six nations see China primarily as a source of economic opportunity, but many have concerns about China's regional goals. They want China to be engaged regionally in productive ways but do not want to allow it to become dominant. They find U.S. security commitments reassuring, bolstering their ability to engage China with confidence. The six nations clearly want U.S. involvement in the region to continue--but sometimes only in certain ways, at certain times, and on particular issues. Thus, they are pulling China closer for the economic opportunities it offers and the United States closer for the general reassurance its long-standing power and influence provide.--Publisher description.